Factors in the spread of brown planthopper, Nilaparvata lugens (Stal.) outbreaks in Central Thailand - Panapanaan, Virgilio M.; Suthad Setboonsarng; Weber, Karl E.; Waibel, Hermann; Demaine, Harvey; Deutscher Akademischer Austauschdienst; Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1991)
The Brown planthopper outbreak in Sri Prachan District was studied to evaluate its impact to the farmers' rice production system. With the varying degrees of infestation in the study area, an estimated damaged area out of 7,471 rai total rice cultivated area during the crop year 1990 was about 3,815 rai which is 51.66%. Analysis of the outbreak revealed that the popular cultivation of RD 23 in wet season and Suphan 60 in the dry season favored the BPH massive increase. The increased use and misuse of pesticide particularly monocrotophos and pyrethroid aggravated the situation. However, as to fertilizer usage of the farmers, though kinds and rates varied across locations, it was not a clear indication that it directly influence the BPH infestation, but its greening effects explicitly suggests that it could enhance or trigger the insect pest BPH. Farmers ultimate response to BPH problem is indiscriminate spraying of chemicals. Variations as to farmers pesticide preferences, rates and timing of application explains for itself why the severity also varied from highly affected area down to the least affected area. The attitude of the farmers towards government provision and control measures is favorable but insufficiency of control measures is the common feedback by most farmers. The governments' response towards BPH problem is so dramatic at the national level, that is, featured by immediate provision of necessary control measures and policy approvals. Village magnification of government assistance reflected that there seemed to be a slow pace in extension process as reflected by low percentage of farmers who received the assistance during the BPH infestation. The insufficiency of control measures given and distribution disparities across villages also speaks for extensions' relative inefficiency.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Planthoppers -- Thailand, Central